Pengaruh Kepemimpinan, Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Dosen Universitas Serambi Mekkah - Jalaluddin Jalaluddin; Sri Mifayetti; Zainuddin Zainuddin (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to find the influence of leadership, organizational culture, organizational commitment, job satisfaction on the performance of the lecturers at Serambi Mekkah Aceh University, totaling 270 people. The sample collection technique used proportional random sampling in order to obtain a sample of 152 people. The data were collected using a questionnaire filled out by respondents from Serambi Mekkah University lecturers. The data analysis technique was carried out in two stages, namely descriptively and inferential. The results showed that: leadership (X1) and organizational culture (X2) had a direct and positive effect on organizational commitment (X3); leadership (X1), organizational culture (X2) and organizational commitment (X3) have a direct and positive effect on job satisfaction (X4); leadership (X1), organizational culture (X2), organizational commitment (X3) and job satisfaction (X4) have a direct and positive effect on lecturer performance (X5). Based on the research results, a fixed model is found that describes the structure of the causal relationship between the variables of leadership, organizational culture, organizational commitment and job satisfaction on the performance of lecturers in the performance model of Universitas Serambi Mekkah lecturers in Banda Aceh.